A culture of deference Congress's failure of leadership in foreign policy - Weissman, Stephen R. (Basic Books, 1995)
A Culture of Deference is filled with revelations about both Congress and American foreign policy. The author traces the development of a set of norms and beliefs - "a culture of deference" - that has confined Congress to the margins of power and caused American interests to suffer around the globe. A legacy of fifty years of hot and cold war, this powerful but often unseen web of internal customs helps generate bipartisan obeisance to the president as well as to narrow-based "special interests." The book portrays the workings of this phenomenon in the Carter, Reagan, Bush, and Clinton admistrations via fresh analyses of Congress and U.S. policy regarding El Salvador, Angola, Nicaragua, Zaire, Iraq, Bosnia, and Somalia. Weissman also shows how exceptional bipartisan leadership and emergent broadbased political constituencies occasionally enable Congress to transcend its predominant culture.